Systematic Review of Bibliography Studies: A Meta-Analysis of Facebook Advertising - Dwianto, Rahmad Agus; Darmawan, Arief Bakhtiar; Haryono, Tulus; Rianto, Rianto; Santoso, Joko (Global Komunika : Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
This article aims to systematically understand the study of Facebook advertising. Facebook is one of the social media that has a large number of users and continues to increase every day. Facebook ads are ads with a wide reach that can reach the target of 1 billion users worldwide. There has been a lot of research on Facebook advertising in the last five years. Previous research conducted by researchers was related to field case studies and data directly related to the use of Facebook advertising. This study uses another approach, namely using a bibliographic study with indexed scientific articles to map topics, themes, and findings related to Facebook advertising. It is necessary to study the topic of Facebook ads because Facebook still has the largers users of social media worldwide. The research method uses literature reviews from various recent studies on the use of social media Facebook using NVivo and VOSviewer tools. The mapping stage in this study was carried out through the imported into the VOSviewer and NVivo 12 plus software. This process is carried out to obtain data clusters, and visualize networks from the research theme. Meanwhile, the Nvivo 12 plus software is used to input the study topic, the relevance of the study themes, and the mapping.